Pengaruh Bukti Fisik terhadap Citra Merek pada Hotel Amaroossa Grande Bekasi - Putri Maya Komalasari; Firdaus Suwarta (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
Physical evidence is one of the important things that can improve customer impressions in using the services provided. Therefore, in running its business, the Amaroossa Grande Bekasi hotel must pay attention to the physical evidence of the hotel so that it is always in good condition, starting from the interior and furniture to the facilities available at the hotel. That way, the impression or perception of guests staying at the hotel will increase and will later create a brand image of the hotel. The purpose of this study is to find out whether physical evidence affects brand image at the Amaroossa Grande Bekasi Hotel, and the method used is a quantitative method with data collection techniques using questionnaires, observations, and literature studies. The number of samples in this study is 100 people who stayed at the Amaroossa Grande Bekasi Hotel. From the calculation of the coefficient of determination (R2), it is known that the effect of physical evidence on brand image is 42.6%. While the results of the t-test calculation obtained the value of tCount>tTable, namely 8,526>1,984 with a sig value of 0,000<0,05, meaning that H1 is received and H0 is rejected. Therefore, it can be concluded that the physical evidence variable has an effect significantly to the brand image at Amaroossa Grande Bekasi Hotel.